Sexting Motives and risk in online sexual self-presentation (Palgrave Studies in Cyberpsychology, 2018)
In the current debate around sexting, this book gives a nuanced account of motives, contexts and possible risks of intimate digital communication. The authors discuss how social media shapes new dating opportunities through apps and dating sites and how sexting fits within an individual's relational and sexual development. They examine the relationships between sexting, health and sexual risk behaviors; and focusing on adolescents, further highlight which role parents can play in relational and sexual education. Chapters cover topics such as abusive sexting behaviours in the context of dating violence and 'slut shaming', media discourses concerning sexting and the legal framework in several countries that shape the context of sexting. This edited collection will be of great interest to academics and students of communication studies, psychology, health sciences and sociology, as well as to policy makers and those interested in current debates on how social media is used for intimate communication. .